A cultural analysis of eco-Islam: How young German Muslims live religion through environmental activism - Willms, Claudia (HTS teologiese studies, 2021)
Eco-Islam is often discussed from a theological perspective, but there are hardly any studies on the activist’s practices, their experiences and reasoning. In order to fill this gap and to emphasise the importance of studying lived religion, this article presents three interviews with young Eco-Islam activists in Germany. By using the method of cultural analysis, the author compares, summarises and abstracts their statements and activities, so that a comprehensive configuration is revealed. Cultural analysis focuses on cultural constellations and tries to think historical, social and biographical components together. To understand the Eco-Islam activist’s perspectives at a deeper cultural level, the author firstly represents a thick description of the statements and activities of her three respondents. Afterwards, she scrutinises the actors’ practices and processes by applying the dimensions of belief, practice and community on their everyday life and performative action. At last she filters three related themes on a cultural constellational level.Contribution: In this article, the author simultaneously highlights the implicit connections of eco-Islamic Activism to aspects of Othering and empowerment, aspects of (re-) interpretation of religious norms and aspects of transgressing environmental activism and the idea of an Islamic community.